Perfromance of an improved solar car ventilator - Saidur, Rahman; Masjuki, Haji Hassan; Hasanuzzaman, M. (International Journal of Mechanical and Materials Engineering, 2009)
The ventilator inhales fresh air from outside into the inside cabin of a vehicle and exhales hot air to the outside. On a sunny day, solar energy can be used to run the ventilator, and to charge the battery simultaneously. During a cloudy day, the ventilator can be driven by the battery. In this paper, heat transfer and energy balance inside the car were investigated. Moreover power consumption of the motor, power produced from the solar panel, radiation effect and battery charging time were investigated. The present study suggests that the motor in the existing ventilator should be replaced by a high speed motor. It is found that more electricity is needed for high speed motor in an improved ventilator. In this paper, a commercially available ventilator has been modified to improve its performance. The modification has increased air flow rate from 20 cfm to 110.5 cfm. The improved ventilator provided at least 11 better result of reducing the temperature inside a car compared to the existing one.